Implementation and performance in New American Schools : three years into scale-up - Berends, Mark, 1962- (RAND, 2001)
Spurred by the piecemeal approach to school reform that had produced little change in the nation's test scores, New American Schools (NAS) launched its efforts for whole-school reform in 1991. As a private nonprofit organization, NAS's mission is to help schools and districts dramatically raise the achievement levels of large numbers of students by using whole-school designs and design team assistance during the implementation process. NAS is currently in the scale-up phase of its effort in which the designs are being widely diffused in partnering jurisdictions across the nation. This book provides an overview of the progress in implementation and performance in a longitudinal sample of schools three years into the scale-up phase. It describes trends in implementation, school performance, and related factors for the sample of NAS schools. Overall, the authors' analyses strongly underscore the importance of both the district environment and design team assistance in implementation. Without leadership, support, and availability of resources at the district level; without clear communication, provision of materials and staff support; and without efforts on the part of design teams to build a consensus of teacher support, implementation is likely to fail or at least lag far behind. Their findings also suggest comprehensive school reforms face many obstacles during implementation, and because of this, whole-school designs face continuing challenges in dramatically raising the achievement of all students.
"Prepared for New American Schools."
"This report was written under the aegis of RAND Education"--Page iv.
Keywords: New American Schools (Organization); School improvement programs -- United States -- Longitudinal studies.; Educational change -- United States -- Longitudinal studies.; Enseignement -- Réforme -- États-Unis -- Études longitudinales.; EDUCATION -- Administration -- General.; Educational change; School improvement programs; United States; Theory & Practice of Education.; Education.; Social Sciences.; Längsschnittuntersuchung; Schulentwicklung; USA; Longitudinal studies